Comportamento da cana-de-açúcar em duas safras e atributos físicos do solo, sob diferentes tipos de preparo - Silva Junior, Carlos Antonio da; Carvalho, Laercio Alves de; Centurion, Jose Frederico [UNESP]; Almeida de Oliveira, Emidio Cantidio (Univ Federal Uberlandia, 2013)
The tillage comprises on average 25% of the cost of deploying a reed, so this cost reduction measures are desirable since they do not compromise the quality of the operation and longevity of sugarcane. The objective was to evaluate the effect of different tillage systems in Acrustox, correlating soil physical properties and characteristics of sugarcane agroindustrial plant cane and ratoon cane. We used five types of soil tillage, over experimental design in blocks with five replications. The particle size was measured every 0.1 m to 0.4 m depth, through deformed soil samples collected at the end of the first growth cycle of the culture. For other soil physical properties: bulk density, total porosity and water content, assessments were performed at the end of each cycle, collecting soil samples in layers of 0-0.20 to 0.21-0.40 m, in addition to performing the penetration resistance, using a penetrometer impact. The response of sugarcane depending on the types of tillage was determined from the evaluation of productivity per hectare of stem (TCH), sugar (TPH), the values of pol % cane (AP), sugar total recoverable (ATR) and fiber samples collected at harvest stalk of sugarcane plant and ratoon cane. In the tillage studied, there was a change of the physical attributes of the soil, causing reduced productivity in 2009/2010 crop, compared with the 2008/2009 season. In tillage system of furrowing direct lowest result was observed for TCH, especially in 2009/2010 crop, when the difference with conventional tillage was 20.53 Mg ha(-1).

O preparo do solo compreende em média 25% do custo de implantação de um canavial, portanto, medidas para redução deste custo são desejáveis desde que não comprometam a qualidade desta operação e a longevidade do canavial. O objetivo foi avaliar o efeito de diferentes sistemas de preparo num LATOSSOLO VERMELHO distrófico, correlacionando atributos físicos do solo e características agroindustriais da cana planta e da cana soca. Foram utilizados cinco tipos de preparos do solo, distribuídos em delineamento experimental em blocos ao acaso, com cinco repetições. A granulometria foi avaliada a cada 0,1 m até a profundidade 0,4 m, por meio de amostras de solo deformadas coletadas no final do primeiro ciclos de crescimento da cultura. Para os demais atributos físicos do solo: densidade do solo, porosidade total e teor de água, as avaliações foram realizadas no final de cada ciclo, coletando amostras indeformadas nas camadas de 0-0,20 m e 0,21-0,40 m, além da realização da resistência mecânica à penetração, utilizando-se de penetrômetro de impacto. A resposta da cana-de-açúcar em função dos tipos de preparo do solo foi determinada a partir da avaliação da produtividade por hectare de colmo (TCH), de açúcar (TPH), bem como dos valores de pol % (AP), açúcar total recuperável (ATR) e fibra de amostras de colmo coletadas na colheita da cana planta e cana soca. Nos preparos estudados, houve alteração dos atributos físicos do solo, provocando redução da produtividade na safra 2009/2010, quando comparada com a safra 2008/2009. No sistema de preparo de sulcação direta foi observado menor resultado de TCH, principalmente na safra 2009/2010, quando a diferença com o preparo convencional foi de 20,53 Mg ha-1.
Behavior of sugarcane in two crops and physical attributes of soil under different tillages
Keywords: Technological aspects; Soil conservation; Bulk density; Total porosity; Penetration resistance; Saccharum spp.